Mizzou today - Hill, Rob, 1954- (University of Missouri Press, 2007)
"The University of Missouri's rich record of accomplishment and service to Missouri, the nation, and the world is captured in this collection of photographs of campus landmarks, people, events, and Tiger spirit. Includes a history of the campus and timelines of key milestones and achievements"--Provided by publisher.